The effect of masks on the visual preference for faces in the first year of life. (15th December 2022) - Galusca, Cristina Ioana; Clerc, Olivier; Chevallier, Marie; Bertrand, Caroline; Audeou, Frederique; Pascalis, Olivier; Fort, Mathilde
Abstract: To prevent the spread of COVID‐19, face masks were mandatory in many public spaces around the world. Since faces are the gateway to early social cognition, this raised major concerns about the effect face masks may have on infants' attention to faces as well as on their language and social development. The goal of the present study was to assess how face masks modulate infants' attention to faces over the course of the first year of life. We measured 3, 6, 9, and 12‐month‐olds' looking behavior using a paired visual preference paradigm under two experimental conditions. First, we tested infants' preference for upright masked or unmasked faces of the same female individual. We found that regardless of age, infants looked equally long at the masked and unmasked faces. Second, we compared infants' attention to an upright masked versus an inverted masked face. Three‐ and 6‐month‐olds looked equally long to the masked faces when they were upright or inverted. However, 9‐ and 12‐month‐old infants showed a novelty preference for the inverted masked face. Our findings suggest that more experience with faces, including masked faces, leads to efficient adaptations of infants' visual system for processing impoverished social stimuli, such as partially occluded faces.